(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Purpose of the present paper was to study the characteristics of eye movements in individuals residing in the anti-terrorist operation area and to compare those with eye movements in healthy individuals. Material and Methods. The study involved patients undergoing outpatient examination: Study group, 120 individuals residing in the ATO zone; Control group, 80 individuals residing in Odessa and Odessa Region. The patients were selected for additional examination at presentation by doctors in outpatient department if the patient’s behavior was a matter of concern for a doctor. The patients were examined accommodation, convergence, conjugate eye movements in 9 eye positions, and horizontal and vertical saccades. Results. The individuals residing in the ATO zone had conjugate eye movement disorders (44.8%), decreased mean values of accommodation (39.8%) and convergence (45%), and impaired visual acuity. Among saccade disorders, hypermetric saccades were most frequently recorded: 25% vs.6.2% in Study and Control groups, respectively, р = 0.0035. Conclusion. The individuals, residing in the ATO area had impaired visual function (visual acuity, convergence, and accommodation) comparing to those residing in Odessa and Odessa region. Significant disorders revealed in vergence and conjugate eye movements, accommodation, and saccades in Study group can be used as objective signs of PTSD.